2006
DOI: 10.1002/ijc.21734
|View full text |Cite
|
Sign up to set email alerts
|

TAK1‐mediated stress signaling pathways are essential for TNF‐α‐promoted pulmonary metastasis of murine colon cancer cells

Abstract: We have recently established a TNF-a-promoted metastasis model, in which the ability to metastasize to the lung was enhanced by stimulation of cultured colon 26 cells with TNF-a before intravenous inoculation. To investigate intracellular events in metastatic cascades of TNF-a-treated cancer cells, we have focused on the stress signaling pathways to c-Jun N-terminal kinase (JNK) and p38. Treatment with a specific inhibitor, SP600125 or SB203580, in vitro suppressed TNF-a-induced migration and pulmonary metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…It was assumed that lung metastasis was not significantly enhanced following etanercept treatment in the present study, as etanercept exhibited little effect on NK cells. This finding does not conflict with previous studies reporting that TNF blockade inhibits carcinogenesis and cancer metastasis (41,42).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It was assumed that lung metastasis was not significantly enhanced following etanercept treatment in the present study, as etanercept exhibited little effect on NK cells. This finding does not conflict with previous studies reporting that TNF blockade inhibits carcinogenesis and cancer metastasis (41,42).…”
Section: Discussionsupporting
confidence: 68%
“…Etanercept has been reported to reduce the number and size of tumors in a spontaneous colon cancer mouse model associated with chronic colitis (40). Furthermore, blockade of TNF-α has been reported to inhibit lung metastasis in a mouse model (41,42). Concerning the effect of etanercept on NK cells, etanercept was reported to inhibit the production of transforming growth factor (TGF)-β1, which subsequently led to the inhibition of NK cells and cytotoxic activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…TAK1 has also been shown to participate in intracellular events involving the T-cell receptor, B-cell receptor, and LMP1 oncogene product of EBV (27 -29). We have recently reported that intermolecular autophosphorylation at Thr 187 is involved in the TNF-a-induced activation of TAK1 in HeLa cells (30), and the activation of TAK1 is essential for TNF-a-promoted pulmonary metastasis in murine colon carcinoma cells (31). Recently, it has been reported that suppression of the p65, JNK, and p38 signaling pathways in a kinase-inactive mutant of TAK1 increased the sensitivity of cells to apoptosis, indicating that TAK1 plays a crucial role in cell survival signaling (32).…”
Section: Introductionmentioning
confidence: 99%
“…This factor is thus essential for preventing injury-associated intestinal ulceration and colitis (25,26). Moreover, TAK1 is also essential for metastasis and tumor cell migration in addition to enhanced cell proliferation and survival (27). Deficiency in RhoA downstream of TAK1 suppresses tumor cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%